CLINICAL AND MORPHOLOGICAL FEATURES AND PROGNOSTIC FACTORS IN BREAST CANCER PATIENTS (The New Uzbekistan Journal of Medicine, 2025)
Breast cancer remains one of the most common malignant tumors among women and ranks among the leading cancer morbidities. The aim of this study was to evaluate the clinical and morphological features and identify key prognostic factors in breast cancer patients. A retrospective analysis of the medical records of 120 patients treated in oncology departments was conducted. Age and clinical characteristics, histological tumor types, tumor differentiation grade, receptor status (ER, PR, HER2), and the Ki-67 proliferation index were examined. The results showed that hormone receptor-positive tumors have a more favorable prognosis, while HER2-positive and triple-negative tumors are characterized by an aggressive course and poor survival. These findings may contribute to improved risk stratification and individualized therapy for breast cancer patients.